10 days in a madhouse [videorecording (DVD)] : the real life experience of Nellie Bly - Hines, Timothy; Barry, Caroline; Lambert, Christopher, 1957-; LeBrock, Kelly, 1960-; Bly, Nellie, 1864-1922 (Broad Green Pictures, 2017)
It is the stunning true story of journalist Nellie Bly's now-legendary undercover stint in a mental hospital in 1887. This dramatic biopic follows a 23-year-old Bly, a fledgling and preternaturally talented news writer looking to expose rampant abuse, corruption, murder and gross mistreatment of patients at the insane asylum in a mental hospital known as Blackwell's Island. To gain access to the asylum, however, Bly must first convince the requisite authorities that she is insane.